Demand-based dimensioning of compressed air systems for energy optimization and flexibility - Javied, Tallal; Kimmig, Florian; Franke, Jörg (Proceedings - 2018 4th International Conference on Control, Automation and Robotics, ICCAR 2018, 2018)
Due to high energy prices in Germany, manufacturing companies have an incentive to increase energy efficiency in production. Compressed air systems (CAS) offer high energy savings potentials. Studies show that CAS are poorly dimensioned in most cases. This paper describes the energy saving potential of compressed air systems. Additionally the importance of not only energy efficiency but energy flexibility is considered. To optimize the current systems and to determine need-based determination of CAS, a Software-tool was developed based on visual basic for application and MS Access. This tool is described in this paper. Different studies estimate a savings potentials due to efficient dimensioning at more than 15%. The described tool helps users identify their energy saving and flexibility potential and suggests CAS configuration to utilize the given potential. It illustrates different investment scenarios based on user-specific requirements. Users can evaluate alternatives that suit their needs based on different KPIs. This tool is designed for SMEs in order to allow them to analyze their CAS without requiring costly external consultation. Energy flexible CAS can enable users to Buy energy at lower costs and use it when prices are high. A smart factory can manage these control challenges independently and utilize the form of energy which is situationally most favorable. Thereby, both economical advantage and energy flexibility can be ensured.
CRIS-Team Scopus Importer:2023-03-07
Keywords: component; compressed air system; energy efficieny; energy flexibility